Design and engineering of zinc-finger domains - Matthews, Jacqui (Henry Stewart Talks, 2007)
Introduction to zinc finger domains, Designer zinc-fingers: de novo design and engineering, Zinc-fingers and DNA binding, Designer zinc-fingers: DNA-binders, polydactyl approach, Designer zinc-fingers: protein-binders
Updated at 2017/04/30